Scalapino, Robert A. y George T-Yu, Modern China and its Revolutionafy Process, Recurrent Challenges to the Traditional Order, 1850-1920, Berkeley, University of California Press, 1985, 814 pp. - Connelly, Marisela (Estudios de Asia y África, 1987)
-